Difficulty in initiating sleep is associated with poor morning cardiovascular function. (January 2021) - Tsai, Hsin-Jung; Kuo, Terry B J; Yang, Albert C; Tsai, Shih-Jen; Yang, Cheryl C H
Highlights: Having sleep initiation difficulty can significantly affect morning cardiovascular function. Reduced vagal tone, blunted baroreflex sensitivity, and elevated blood pressure presented in the morning among sleep-onset insomnia. Autonomic nervous system dysregulation in the morning may be a possible link between sleep-onset insomnia and high risk of cardiovascular events. Abstract: Insomnia is a risk factor for hypertension and cardiovascular events, and this association is strongest for sleep-onset insomnia. This study explored morning cardiovascular function in individuals with sleep-onset insomnia by analysing heart rate variability (HRV), blood pressure variability, and baroreflex sensitivity. Sleep quality of fifteen good sleepers and 13 individuals with sleep-onset insomnia was measured by overnight polysomnography, followed by continuous recordings of the participant's blood pressure and heart rate for 10 min immediately after they had woken up the following morning. After morning awakening (averaged time: 12.33 ± 10.48 min), a significantly reduced vagal tone assessed by HRV, including lower total power of HRV, lower high frequency of HRV, and elevated slopes of systolic as well as diastolic blood pressure in the morning with a blunted baroreflex sensitivity in the insomnia group were noted, compared to the control group. No differences in sympathetic-related activity were observed. The regulation of cardiovascular activity by the parasympathetic nervous system plays an important role in sleep-onset insomnia. Weak vagal modulation and blunted baroreflex sensitivity were evident in this insomnia subtype, which indicates that difficulty in initiating sleep can independently affect morning cardiovascular function.